2021
DOI: 10.1097/mao.0000000000003329
|View full text |Cite
|
Sign up to set email alerts
|

Transmastoid Occlusion Surgery for Superior Semicircular Canal Dehiscence Syndrome Improves Patient-Reported Quality-of-Life Measures and corrects cVEMP Thresholds and Amplitudes

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Over time, from 3-month to 2-year follow-up, there was a statistically significant decline in THI score ( p = 0.01). The median HHI total score improved from 23 (IQR, 12-29) to 9 (1-19) at 1-year follow-up ( p = 0.04; CI, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. There was no statistically significant change in HHI score over time from the 3-month to 2-year follow-up ( p = 0.73).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Over time, from 3-month to 2-year follow-up, there was a statistically significant decline in THI score ( p = 0.01). The median HHI total score improved from 23 (IQR, 12-29) to 9 (1-19) at 1-year follow-up ( p = 0.04; CI, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. There was no statistically significant change in HHI score over time from the 3-month to 2-year follow-up ( p = 0.73).…”
Section: Resultsmentioning
confidence: 91%
“…Note that the median change was within what Jacobson and Newman (20) considered test-retest variability (significant change ≥18 points). In the cohorts of Crane et al (7), Jung et al (6), and de Wolf et al (9), postoperative mean DHI scores were 18 (standard deviation, ±15; range, 0-54), 32 (range, 0-98), and 27 (CI, [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Although both preoperative and postoperative DHI scores in our cohort are lower, two aspects are in line with previous literature: 1) Crane et al did not find significant improvement in DHI scores for patients with preoperative DHI <30, and 2) postoperative, symptoms of dizziness are more prevalent than autophony (6,7,9,10).…”
Section: Symptoms Of Autophony Resolve More Readily Thanmentioning
confidence: 98%
See 2 more Smart Citations
“…In 1998, Minor et al (1998) first reported eight cases of SCDS, and since then, many cases of SCDS have been reported (Steenerson et al, 2020;de Wolf et al, 2021;Kontorinis and Gaggini, 2021;Nieto et al, 2021;Ellsperman et al, 2022). The incidence of SCDS is low and its pathogenesis is unknown, and it may be related to head trauma, infection, and pathological changes in the middle ear or adjacent structures (Rosowski et al, 2004;Ward et al, 2017;Mau et al, 2018).…”
Section: Application Of Semicircular Canal Occlusion In Treatment Of ...mentioning
confidence: 99%